Maternal Health Care Seeking Behavior for Neonatal Danger Signs and Associated Factors Among Post-Partum Mothers in Southeast Ethiopia: A Cross-Sectional Study. (December 2022) - Gomora Tesfaye, Degefa; Geta, Girma; Kene, Chala; Seyoum, Kenbon; Tekalegn, Yohannes; Desta, Fikreab; Sahiledengle, Biniyam; Atlaw, Daniel; Ejigu, Neway; Negash, Wogene
Early health care seeking could save neonates' lives and have a significant role in decreasing neonatal death, while delayed health care seeking has many contributions to neonatal mortality. Therefore, this study aimed to assess maternal health-seeking behavior for neonatal danger signs and associated factors among postpartum mothers in Southeast Ethiopia. A community-based cross-sectional study was conducted on a random sample of 400 women with sick neonates from June 1st, 2020 to 27th, November. A Modified Anderson and Newman behavioral model consisting predisposing, enabling, need, and health system factors were utilized and participants were interviewed by using structured questionnaires. Multivariate logistic regression analysis was used to identify factors associated with maternal health-seeking behavior. Adjusted odds ratios (AOR) were reported with their corresponding 95% confidence interval (CI) to determine the strength of the association. The statistical significance was declared at P < .05. Slightly higher than two-fifths, (44%, 95% CI: 39.2-48.9) of the respondents' have appropriate healthcare-seeking behavior for neonatal danger signs. Postnatal care follows-up (AOR = 3.5; 95% CI: 2.06-5.80), good knowledge of neonatal danger signs (AOR = 2.78; 95% CI: 1.63-4.73), decision-making power for taking sick neonates to health institution (AOR = 3.02, 95% CI: 1.61-5.67), mothers living with their partner (AOR = 3.00; 95% CI: 1.42-6.31), and health insurance (AOR = 1.82; 95% CI: 1.08-3.06) were significantly associated with having appropriate healthcare-seeking behavior. Healthcare-seeking behavior of the respondents' was low and indicated by nearly 2 out of 5 respondents' had appropriate health-seeking behavior for neonatal danger sign. Postnatal care follow-up, health insurance, good knowledge of neonatal danger signs, living with a partner, and decision-making power were predictors of appropriate healthcare-seeking behavior for neonatal danger signs. Emphasis should be given to creating awareness of neonatal danger signs, maintaining postnatal follow-up, and encouraging mothers/caregivers to make immediate decisions for seeking healthcare at healthcare institutions.